Families’ opinions about their involvement in care during hospitalization: a mixed-methods study - Josien M. Woldring; Wolter Paans; Reinold O. B. Gans; Hinke M. van der Werf; Marie Louise Luttik (BMC Nursing)
Abstract Background Healthcare professionals in the hospital setting frequently assume primary caregiving responsibilities, which often leads family members to perceive this as standard practice during hospitalization. This dynamic may create a gap between actual and desired levels of family involvement. The aim of this study is to explore the opinions of families about their involvement in care during the hospitalization of a relative. Methods A sequential explanatory mixed-method study design was used, where quantitative data collection is followed by qualitative data collection for a deeper understanding of the quantitative findings. Data were collected between November 2023 and April 2024 across 15 wards in a university hospital in the north of the Netherlands. 153 family members of hospitalized patients completed the adapted Families’ Importance in Nursing Care–Families’ Opinions questionnaire, providing valuable quantitative data. Twenty-three of these family members were subsequently interviewed to gather qualitative insights. Data were analyzed sequentially, with the quantitative results guiding qualitative data collection. The two types of data were integrated to draw comprehensive conclusions about the significance of family involvement during hospitalization. The study adhered to the guidelines of the Good Reporting of A Mixed Method Study (GRAMMS). Results The questionnaire scores indicate a high willingness for involvement in care during hospitalization. Subsequent in-depth interviews led to the development of a model demonstrating that this involvement is sequentially related to the themes of acknowledgement, alignment, and collaboration. Conclusions Family members expressed a need to be acknowledged by healthcare professionals as partners in care. Role agreements and information sharing during hospital care should be aligned to achieve effective collaboration between family members and healthcare professionals.